2001
DOI: 10.1002/path.876
|View full text |Cite
|
Sign up to set email alerts
|

Inter-observer variation between general and specialist gastrointestinal pathologists when grading dysplasia in ulcerative colitis

Abstract: Histological dysplasia is the cornerstone of colorectal cancer surveillance in ulcerative colitis (UC). Recently, pathologists have received unfavourable media attention concerning other cancer screening programmes. The aim of this study was to determine whether colonic biopsy specimens should be examined by gastrointestinal pathologists as opposed to generalists, by examining inter-observer variation between the two groups. Fifty-one coded slides showing varying degrees of dysplasia were mailed to seven gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
1
9

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(127 citation statements)
references
References 38 publications
(38 reference statements)
7
109
1
9
Order By: Relevance
“…There is still no consensus on management in cases of unifocal or multifocal low grade dysplasia (LGD) in flat mucosa. What complicates the issue, as earlier studies have indicated, is that there seems to be difficulty in confirming dysplasia by the pathologist [7,8] . The management of the different forms of dysplasia varies from no management or intensifying the screening program to immediate colectomy.…”
Section: Introductionmentioning
confidence: 74%
“…There is still no consensus on management in cases of unifocal or multifocal low grade dysplasia (LGD) in flat mucosa. What complicates the issue, as earlier studies have indicated, is that there seems to be difficulty in confirming dysplasia by the pathologist [7,8] . The management of the different forms of dysplasia varies from no management or intensifying the screening program to immediate colectomy.…”
Section: Introductionmentioning
confidence: 74%
“…Also the histological evaluation of the biopsies encounters uncertainty. There is a considerable variability in the diagnosis of low or high-grade dysplasia among pathologists (inter-observer variability) and also on a second reading of the same slide by the same pathologist (intra-observer variability) [20,73,74]. The subgroup of patients who develop cancer within eight years disease duration, that is, before guidelines recommend inclusion in surveillance programs might be erroneously excluded from surveillance [75].…”
Section: The Management Of Cancer Risk In Ibdmentioning
confidence: 99%
“…Instead, epithelial dysplasias have been defined as precursor lesions and are meant to be the most predictive feature of intensive and expensive surveillance programs today (Collins, Feldman, and Fordtran 1987). However, reliable endoscopic sampling and histopathological evaluation is difficult (Eaden et al 2001;Riddell 1998;Lynch et al 1993). Additionally, a review of 12 surveillance studies with 92 detected carcinomas in 1,916 patients revealed that about half of them were advanced Dukes´ C and D malignancies and only 12% were early stage carcinomas (Lynch et al 1993).…”
Section: Colorectal Cancer Risk In Ulcerative Colitismentioning
confidence: 99%